(untitled) (Journal of Engineering, 2011)
In the present study, a low cost adsorbent is developed from the naturally available sawdust which is biodegradable. The removal capacity of chromium(VI) from the synthetically prepared industrial effluent of electroplating and tannery industrial is obtained. Two modes of operation are used, batch mode and fixed bed mode. In batch experiment the effect of Sawdust dose (4- 24g/L) with constant initial chromium(VI) concentration of 50 mg/L and constant particle size less than1.8 mm were studied. Batch kinetics experiments showed that the adsorption rate of chromium(VI) ion by Sawdust was rapid and reached equilibrium within 120 min. The three models (Freundlich, Langmuir and Freundlich-Langmuir) were fitted to experimental data and the goodness of their fit for adsorption was compared. In the fixed bed isothermal adsorption column, the effect of particle size (dp) (1.09- 1.8) mm, influent flow rate (Q) (1- 4) L/hr, bed depth (H) (25- 35) cm and the pH(1-7)of the solution were studied .The results show that Sawdust is an efficient adsorbent for the removal of Cr(VI) from wastewater. Percent removal of chromium reaches (100%) with increasing of contact time and decreasing the pH.UV- Spectrophotometer was used to determine the metal ion concentration